EUROPEAN EXPERIENCE PROTECTION OF THE RIGHT TO ENTREPRENEURSHIP BY MEANS OF JUDICIAL ADMINISTRATIVE JURISDICTION - Ryabchenko, Vasily (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to substantiate the optimal legal form and means of protection of the right to entrepreneurship by an administrative court, based on the European experience of exercising administrative jurisdiction in public law disputes arising from legal relations in the field of entrepreneurship. Research methods: the study used general scientific and special methods. In particular, the dialectical method reveals the general connection between the specifics of relations in the field of entrepreneurship and the development of procedural forms of protection of the right to entrepreneurship in administrative proceedings. Special methods include: the comparative legal method, which was used to compare the substantive law provisions of national legislation of Ukraine and Germany, France, Belgium, as well as scientific categories, definitions and approaches. The historical and legal method made it possible to reveal the essence of the protection of the right to entrepreneurship in administrative proceedings and provided the basis for the author’s view on certain problematic issues. For a comprehensive generalisation of the features inherent in the development of procedural forms of protection of the right to entrepreneurship, the author uses the method of system analysis. Using the normative-dogmatic method, the author analyses the content of the legal acts of domestic and foreign legislation regulating the issue under study. By the method of legal modelling, the author develops proposals for improving the regulatory framework governing the development of procedural forms of protection of the right to entrepreneurship in Ukraine. Results: the article makes a comparative analysis of the problem of forms of protection of the right to entrepreneurship in administrative proceedings in Ukraine and developed European countries (Germany, France, Belgium). For this purpose, a number of legal acts of both countries regulating this issue have been developed. Certain forms of protection of the right to entrepreneurship are defined to entrepreneurship in administrative proceedings. It is established that in countries with well-developed legislative traditions, there is a clear distinction between general and special legislation. General legislation establishes requirements for certain legal procedures, while special legislation establishes such requirements only in exceptional cases. This publication examines general and specific forms of protection of the right to conduct a business in administrative proceedings. It is proved that an effective legal remedy for the protection of the right to entrepreneurship is a "temporary order". As this institution is currently absent in Ukraine, the author analyses Germany’s positive experience to propose its introduction in Ukraine. Discussion: analyses different scientific approaches to determining the forms of protection of the right to entrepreneurship in administrative proceedings. It also covers general issues of forms of administration of justice in administrative cases. However, it does not take into account the specifics of disputed legal relations regarding the exercise of the right to entrepreneurship; general definition of the essence of a public law dispute; public law disputes in the field of economic activity as the subject of administrative proceedings.